Public preferences for conservation of endangered Borneo Pygmy elephant in Sukau Kinabatangan, Sabah, Malaysia - Naim, Shafinaz (2021)
The recent deaths of Pygmy elephants in Sabah have raised concerns about the state's reputation as a nature conservationist. The elephants are becoming increasingly exposed to humans as forests are cleared for development, potentially leading to more conflict between humans and the animals. With only between 1,500 and 2,000 Pygmy elephants left in the wild, conservation efforts are crucial. To protect the Pygmy elephants in Sukau Kinabatangan, a study was conducted to assess public preferences and conservation values for the species. The study objectives: i) to estimate the willingness to pay (WTP) value and preferences for conservation management of Borneo Pygmy elephants, ii) to examine the influence of wildlife value orientation on risk perception, and iii) to investigate the mediation effects of specific positive beliefs between wildlife value orientation and risk perception. This study used the Choice Experiment (CE) method and the Structural Equation Modeling with Partial Least Square (SEM-PLS) to assess the responses of 400 Sukau residents and 401 visitors. The CE method was used to estimate the WTP value and preferences for conservation management of the Borneo Pygmy Elephant, and the SEMPLS was used to examine the influence of wildlife value orientation on risk perception and the mediation effects of specific positive beliefs between wildlife value orientation and risk perception. This study found that local people most preferred attributes is to increase the number of populations to 3,000 with the marginal value of RM4.55 and visitors preferred systematic fencing as the most preferred attribute with the marginal values of RM19.53. This study also found that domination positively influenced risk perception for both local people and visitor respondents. However, the results did not find any support between mutualism and risk perceptions for visitor samples. This indicates that domination wildlife value orientation was related to risk perception in both groups of respondents. Furthermore, the mediation effects of specific positive beliefs between wildlife value orientation and risk perception were also investigated. The study found that mutualism positively influenced specific positive beliefs, specific positive beliefs negatively influenced risk perceptions, domination positively influenced risk perceptions, and domination negatively influenced risk perceptions mediated by specific positive beliefs of Borneo Pygmy elephants. The study recommends policy changes based on the results. As the public is willing to pay for the conservation of Pygmy elephants, policymakers could consider charging a conservation fee in the future based on the most preferred attributes selected by locals and visitors. The study also emphasizes the importance of taking into account human orientation and beliefs when designing conservation programs. The findings suggest that policymakers should design conservation programs that can create more positive perceptions and beliefs about the Borneo Pygmy elephant to avoid extinction in the future.